2022
DOI: 10.1126/sciadv.abm8433
|View full text |Cite
|
Sign up to set email alerts
|

Direct optical patterning of perovskite nanocrystals with ligand cross-linkers

Abstract: Precise microscale patterning is a prerequisite to incorporate the emerging colloidal metal halide perovskite nanocrystals into advanced, integrated optoelectronic platforms for widespread technological applications. Current patterning methods suffer from some combination of limitations in patterning quality, versatility, and compatibility with the workflows of device fabrication. This work introduces the direct optical patterning of perovskite nanocrystals with ligand cross-linkers or DOPPLCER. The underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
103
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 65 publications
0
103
0
Order By: Relevance
“…This strategy relies on the chemical transformation of photoactive (mostly photodecomposable) surface ligands of NCs and the UV light-triggered alteration in NC colloidal stability. Similarly, we and others showed that direct photopatterning of NCs can be achieved by cross-linking their native surface ligands under UV irradiation. Both methods use workflows and infrastructures of well-established photolithography but do not involve conventional photoresists. These resist-free, direct photopatterning approaches yield NC patterns with microscale lateral precision in a parallel fashion, supporting the fabrication of patterned thin-film electronic and optoelectronic devices with high performance. In this regard, the combination of NCs and photoactive ligands/additives can be viewed as the inorganic and functional version of photoresists . However, in contrast to the versatility of photoresists in building structures with widely variable heights (over 6 orders of magnitude, from nanometers to millimeters) and even in 2.5D and 3D formats, these “inorganic photoresists” can only afford patterns with heights restricted below ∼100 nm in a single step .…”
mentioning
confidence: 99%
“…This strategy relies on the chemical transformation of photoactive (mostly photodecomposable) surface ligands of NCs and the UV light-triggered alteration in NC colloidal stability. Similarly, we and others showed that direct photopatterning of NCs can be achieved by cross-linking their native surface ligands under UV irradiation. Both methods use workflows and infrastructures of well-established photolithography but do not involve conventional photoresists. These resist-free, direct photopatterning approaches yield NC patterns with microscale lateral precision in a parallel fashion, supporting the fabrication of patterned thin-film electronic and optoelectronic devices with high performance. In this regard, the combination of NCs and photoactive ligands/additives can be viewed as the inorganic and functional version of photoresists . However, in contrast to the versatility of photoresists in building structures with widely variable heights (over 6 orders of magnitude, from nanometers to millimeters) and even in 2.5D and 3D formats, these “inorganic photoresists” can only afford patterns with heights restricted below ∼100 nm in a single step .…”
mentioning
confidence: 99%
“…For example, using an I – exchange solution, mixed CsPb­(Br/I) 3 arrays were synthesized with Br-rich and I-rich particles represented by green- and red-channel emission, respectively (Figure m). Compared to spatial resolution (∼10–100 μm) of previously reported multiple composition halide perovskite patterning techniques, , our method can be used to make arrays of particles, of deliberately varying composition, with submicron resolution. The high-resolution and high-throughput arrays may prove useful for fabricating a wide variety of devices, including ultra-high-density full-color backlit displays, multicolor photo-detectors, and multilevel data storage technologies.…”
Section: Resultsmentioning
confidence: 99%
“…Colloidal nanocrystals (NCs) are promising materials for high-sensitivity strain gauge sensors owing to their controllable physical properties and solution-based processability [ 11 13 ]. However, conventional lithographic techniques, such as photo- and e-beam lithography, cannot be fully utilized for these NCs because of their reactive surfaces, thereby hindering the patterning of NC thin films and realization of sensor arrays, especially on ultrathin substrates [ 14 16 ]. This impediment significantly limits multiaxial sensitivity and conformal contact on human skin, such as on vocal cords.…”
Section: Introductionmentioning
confidence: 99%